Country Program Policy Research and Capacity Strengthening - Dorosh, Paul (2015)
"IFPRI at 40: Looking Back, Looking Forward" Special Event held on November 18, 2015. Presentation by Paul Dorosh, Director of Development Strategy and Governance Division (DSGD) at IFPRI.